Communication between the elderly person and the Family Health Team: is there integrality? - Rita Tereza de Almeida; Suely Itsuko Ciosak (Universidade de São Paulo, 2013)
OBJECTIVE: to verify the forms of communication used in four Primary Health Units with Family Health Program teams in Porto Feliz, São Paulo, and how they impact in the care and control of the health of elderly people. METHOD: this qualitative study sought to capture the communication between elderly people and healthcare professionals. Interviews were conducted with 20 elderly people of both sexes. RESULTS: from the discourses and observations, assertive communication and blocked communication emerged as the central analysis themes, the verbal and nonverbal elements of which, unveiled subjectivity of the communication process, of the local culture and of the psychosocial factors positively and negatively contributing to the healthcare for elderly people. The nursing teams of the Family Health Strategy showed forms of communication that favored the adherence of the elderly people to the care and control of their health. Negatives aspects did not have completely prejudicial consequences, however, should be avoided, in order to facilitate integral care to elderly people. CONCLUSION: it is worth reinforcing the need for improvement of the nursing team and other healthcare professionals regarding health communication as an innovative technology, bringing credibility to the health promotion and prevention programs with elderly users.